Digitalization of Islamic Philanthropy: Effectiveness of Management of Zakat and Waqf in Contemporary Indonesia - Choirul Mahfud; Rochim Fajri Tsalatin; Lusi Amelia; Nurul Sofia Dewi; Moh Iqbal Fatchurozi; Muhammad Risyad Ibenzani; Fathurahman Agung (Studia Religia : Jurnal Pemikiran dan Pendidikan Islam, 2020)
The digitalization of Islamic philanthropy in Indonesia is a topic that needs to be seen from its effectiveness and efficiency aspects. Moreover, in the era of the Covid-19 pandemic and advances in information technology, zakat and waqf services are one of the central issues to achieve the best goals. This article focuses on case studies with various data from the internet to determine the causes of this problem and effective methods for managing zakat and waqf. In general, this problem's cause is the Indonesian people's lack of knowledge about digital-based management for people's welfare and supporting the country's economy. Good and effective management of zakat and waqf can be realized with computer-based and integrated management compared to manual methods considering that the world has entered the Industrial Revolution 4.0. On the other hand, the community also has optimism that effective management of zakat and waqf can improve Indonesia's economy. Thus, the management of zakat and waqf that involves digital technology is considered to have the potential to increase public trust and the realization of state welfare. Keywords: Philanthropy digitalization; Management Effectiveness; Waqf; Zakat